Expression of a full length Arabidopsis vacuolar H+-pyrophosphatase (AVP1) gene in tobacco (Nicotiana tabbacum) to increase tolerance to drought and salt stresses - Zafar, Shahid Mansoor, Arsalan Yusuf, Zahid Mukhtar, Muhammad Ibrahim, Sher Afzal Khan, Yusuf (Journal of Phytology, 2009)
Among various abiotic stresses salinity and drought are the two major factors limiting the crop productivity. Genetically engineered salt and drought tolerant plants could provide an avenue to the reclamation of farmlands lost to agriculture because of salinity and a lack of rainfall. The Arabidopsis gene AVP1 encodes a vacuolar pyrophosphatase that functions as a proton pump and generates an electrochemical gradient in vacuole, thereby activating vacuolar membrane-antiporters including Na+/H+ antiporter, which helps in sequestration of Na+ into vacuole. In addition, over-expression of AVP1 gene increase vegetative growth by auxin transport and enhances auxin mediated root development, consequently achieving higher water absorption and retention capacities. The goal of present work is amplification of full length AVP1 (3.2kb) gene, from Arabidopsis thaliana genomic DNA through PCR, its cloning into a suitable plant expression vector and transformation in tobacco through Agrobacterium mediated transformation method for its characterization. PCR analysis showed the successful transformation of this gene in Nicotiana tabaccum. Screening of these putative transgenic plants against different salinity levels (50-250mM NaCl) showed that transgenic plants were tolerant to 250mM NaCl whereas the control plants showed wilting within 36-48 hours of salt treatment. Under periodic drought stress treatment transgenic (AVP1) plants were significantly more tolerant than wild type plants. Similarly the results of salinity and drought tolerance experiment in sand under saline and water regime conditions confirmed that introns play a key role in gene expression and regulations and improve the growth of plants. These resistant phenotypes are associated with increased internal stores of solutes.